Enhanced plasmid DNA utilization in transiently transfected CHO–DG44 cells in the presence of polar solvents. (25th August 2015) - Rajendra, Yashas; Balasubramanian, Sowmya; Kiseljak, Divor; Baldi, Lucia; Wurm, Florian M.; Hacker, David L.
Abstract : Although the protein yields from transient gene expression (TGE) with Chinese hamster ovary (CHO) cells have recently improved, the amount of plasmid DNA (pDNA) needed for transfection remains relatively high. We describe a strategy to reduce the pDNA amount by transfecting CHO–DG44 cells with 0.06 μg pDNA/10 6 cells (10% of the optimal amount) in the presence of nonspecific (filler) DNA and various polar solvents including dimethylsufoxide, dimethyl formamide, acetonitrile, dimethyl acetamide (DMA), and hexamethyl phosphoramide (HMP). All of the polar solvents with the exception of HMP increased the production of a recombinant antibody in comparison to the untreated control transfection. In the presence of 0.25% DMA, the antibody yield in a 7‐day batch culture was 500 mg/L. This was fourfold higher than the yield from the untreated control transfection. Mechanistic studies revealed that the polar solvents did not affect polyethylenimine‐mediated pDNA delivery into cells or nuclei. The steady‐state transgene mRNA level was elevated in the presence of each of the polar solvents tested, while the transgene mRNA half‐life remained the same. These results indicated that the polar solvents enhanced transgene transcription. When screening a panel of recombinant antibodies and Fc‐fusion proteins for production in the presence of the polar solvents, the highest increase in yield was observed following DMA addition for 11 of the 12 proteins. These results are expected to enhance the applicability of high‐yielding TGE processes with CHO–DG44 cells by decreasing the amount of pDNA required for transfection. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1571–1578, 2015